Dukungan Keluarga dan Perilaku Deteksi Dini Kanker Serviks Pada Wanita Usia Subur - Shafiatush Shalikhah; Sabar Santoso; Hesty Widyasih (Poltekkes Kemenkes Denpasar, 2021)
ABSTRAKThe achievement of early detection of cervical cancer in the Special Region of Yogyakarta has not yet reached the national target.Based on the Health Profile in 2017,the lowest cervical cancer early detection coverage in Special Region Yogyakarta is in Bantul Regency.Family support is one of the reinforcing factors of cervical cancer early detection behavior.This study aims to determine the relationship between family support and cervical cancer early detection behavior in women of childbearing age. The samples were 100 women of childbearing age who were selected by applying consecutive sampling techniques. Data analysis used chi-square statistical test.The result showed that most of the respondents are 35 – 49 years old (60%),have secondary education (54%),as many as 58 % respondents do not work,most of the respondents received less support from their families (51%) and did not do early detection of cervical cancer (77%).Bivariate analysis showed that there was a relationship between family support and cervical cancer early detection behavior with p-value = 0,000.The relationship closeness correlation in medium category (contingency coefficient =0,420). Advice for midwives to improve counseling on the importance of early detection of cervical cancer and expand the target of promoting early detection of cervical cancer by involving husband/ family.